Glycemic Status of Type 2 Diabetic Subjects On Different Anti-Diabetic Management (BIRDEM Medical Journal, 2017)
Background: Diabetes mellitus (DM) is a complex multi-system disorder that may lead to diabetes specific complications and target organ damage which can be prevented or delayed by good or strict glycemic control. Our aims were to evaluate the glycemic status of adult type 2 DM (T2DM) patients on different anti-diabetic management, to evaluate role of education and economic status on glycemic control and to correlate glycemic status with complications.Methods: This cross-sectional study was conducted in BIRDEM General Hospital from November 2013 to April 2015. Data were collected in a pre-formed data collection form, purposively and consecutively from 300 T2DM patients who were diagnosed as diabetic for 3 months or more and were compliant, after face to face interview and undergoing the required physical examinations. Then data were compiled and analyzed accordingly.Result: Neither the educational level nor the monthly income had any influence on glycemic control. Only 17% of the patients had good glycemic control (HbA1c